WELLS BENCH AND DILLON AND ITS FUNCTIONALITY IN OBTAINING MEASUREMENTS OF THE PHYSICAL COMPONENT FLEXIBILITY (Fiep Bulletin - online, 2012)
The flexibility, as physical quality is of great importance in physical fitness and quality of life of individuals. The sit and reach test proposed by Wells and Dillon is widely used to assess the flexibility of practitioners of various sports and health oriented. However, its use receives critics regarding the correct application of the test, as well as its validity as criteria for checking the flexibility of the lumbosacral region, the coxofemoral joint and hip joint. The aim of this study is to assess the positive or strong and negative or disadvantageous in the application of sit and reach test proposed by Wells and Dillon. For this, a survey was conducted in scientific databases oriented in health and physical activity, that are Scielo, Lilacs and Bireme, based on key words: flexibility, physical assessment, sit and reach test, and consulted both in Portuguese and English and, as time cohort, the period from 2000 to 2011. The strengths of this test were observed: its low cost and accessibility, being a simple test. The negative or disadvantageous: inaccuracy in the application of tests so that no one notices or it is able to flex the knee joint at the time of collection; overcompensation of the glenohumeral joint to achieve a greater distance, the disproportionate length of the trunk to upper and lower members, taking advantage in reaching more distant points. Therefore, we conclude that the test does not show such precision as had been thought to apply it to physical assessments as a totally reliable parameter to check the degree of flexibility of the lumbosacral region, the hip joint and the coxofemoral joint.
Keywords: Flexibility; Physical Evaluation; Sit and reach test